(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2016)
In the Exchanges, we present conversations with scholars and practitioners of community engagement, responses to previously published material, and other reflections on various aspects of community-engaged scholarship meant to provoke further dialogue and discussion. We invite our readers to offer in this section their own thoughts and ideas on the meanings and understandings of engaged scholarship, as practiced in local or faraway communities, diverse cultural settings, and various disciplinary contexts. We especially welcome community-based scholars’ views and opinions on their collaboration with university-based partners in particular and on engaged scholarship in general. In this issue, Nazeem Muhajarine talks with Dr. Bryan Smale about his work on the Canadian Index of Wellbeing. Dr. Smale is Professor, Recreation and Leisure Studies, Faculty of Applied Health Science, University of Waterloo, and Director of the Canadian Index of Wellbeing.